Steady frequency prediction algorithm for power system with governor deadband. (22nd November 2017) - Fan, Chengwei; Teng, Yufei; Xie, Jian; Wang, Xiaoru
Summary: The frequency stability of power system is usually jeopardized by the active power deficit for major disturbances. To deal with these events, adaptive load shedding schemes are effective, and the steady frequency prediction is considered as the prerequisite. However, none of previous predictive methods has taken into consideration the nonlinear segment that may distort system frequency response. This paper investigates the effect of speed governor deadband and presents a method to evaluate its effect on the steady frequency. Based on the wide area measurement system measurements, a predictive algorithm of steady frequency is studied. It utilizes the modified regulation coefficient to consider the governor deadband effect and employs instantaneous measurements of postdisturbance to calculate the steady frequency directly. Simulations on the IEEE‐9 system and a practical system of China have solidified the effectiveness of the proposed algorithm.